Evaluations of an experiential gaming model - Kiili, Kristian (Human Technology, 2006)
This paper examines the experiences of players of a problem-solving game. The main purpose of the paper is to validate the flow antecedents included in an experiential gaming model and to study their influence on the flow experience. Additionally, the study aims to operationalize the flow construct in a game context and to start a scale development process for assessing the experience of flow in game settings. Results indicated that the flow antecedents studied—challenges matched to a player's skill level, clear goals, unambiguous feedback, a sense of control, and playability—should be considered in game design because they contribute to the flow experience. Furthermore, the indicators of the actual flow experience were distinguished.